Identification of orexin-A immunoreactivity in ostrich (Struthio camelus camelus) kidneys - Yaman, Mine; Tarakci, Berrin G.; Bayrakdar, Ali (Univ Zagreb Vet Faculty, 2013)
Orexin-A (hypocretin-1), a neuropeptide, was originally shown to be specifically expressed in the hypothalamus. We studied the presence of orexin-A immunoreactivity in ostrich kidneys. Immunocytochemistry showed that orexin-A immunoreactivity was localized in the tubules of the ostrich kidneys. Immunoreactivity was found both in the renal cortex and the medulla. Immunostaining was mainly localized in the apical border and lumen of tubules.
Keywords: orexin-A; ostrich; kidney; immunoreactivity